Calidad de atención del profesional de enfermería en el servicio de cirugía del hospital Isidro Ayora - Rodríguez Tinitana, Rosario Elizabeth (2014)
The Isidro Ayora Hospital is a secondary hospital that provides health care to the population of Loja, Zamora Chinchipe and part of El Oro, has the service of Surgery, which offers the same attention to healthy and users in different pathologies specialties such as general surgery , neurosurgery, oncology , laparoscopic , ENT , pediatric surgery and reconstructive surgery. The overall objective of this study is to evaluate the quality of care of the nurse in the service of Surgery Hospital Isidro Ayora and compliance have been raised two specific objectives: Identify the major determinants that influence the quality of professional care nursing . Similarly diagnose the degree of user satisfaction regarding the care given by the professional. In this situation it was felt necessary to conduct a study whose primary reason is to assess the quality of care by the nurse , in the same way to provide health team looking for improvements. For the development of this research is the scientific method utilized as a technical survey and the questionnaire as a tool for the statement that was used. The results showed that in 71% the nurse provides a very good quality of care, since 100 % of professionals provides information to the user, plus 71 % provide education to you during your hospitalization and / or perform discharge plan , professionals as well as agree to participate in training . As a result, the nurse recommended the establishment of an evaluation committee of the quality of care , as well as the unification of criteria of professional-user and / or family for the welfare of it. Finally 55 % of users are satisfied regarding the treatment provided by nurses and 94 % stated that professionals act quickly and timely when filing any discomfort so.